The "Abstract to Concrete" Way of Thinking in the Economic Manuscripts 1857-1858 - Chen, Xinghui (Journal of Theory and Practice of Social Science, 2024)
Marx in the "1857-1858 Economic Manuscripts" in the introduction to the study of political economy from the "abstract to concrete" method. Previous political economists used the first path of political economy research "from concrete to abstract", that is, from perceptual concrete to thinking abstract, and the second path is "from abstract to concrete", that is, from thinking abstract to thinking concrete, thinking concrete is The second path is "from the abstract to the concrete", i.e. from thinking abstractly to thinking concretely, and thinking concretely is thinking abstractly which contains the prescriptive nature of difference and opposition.